Protective Mechanism of Alisol A 24-Acetate on Brain Microvascular Endothelial Cells in Mice with Cerebral Ischemia-Reperfusion Injury by TRPM2/Akt/GSK3β Pathway - LI Huihong; DENG Yunfei; WEI Wei; ZHAN Zengtu; LIN Libin; XUE Xiehua (康复学报)
ObjectiveTo explore the mechanism of Alisol A 24-acetate (24A) on improving brain microvascular endothelial cells (BMECs) injury after cerebral ischemia reperfusion in mice.MethodsA total of 45 10-week-old male C57BL/6 mice were randomly divided into sham surgery group, model group and 24A group, with 15 cases in each group. The model group and the 24A group were treated with 20 min bilateral common carotid artery ligation followed by reperfusion to establish a cerebral ischemia reperfusion injury (CI/RI) model, but the common carotid artery and vagus nerve were separated without ligation in the sham surgery group. The 24A group was given 24A through intragastric administration with the dosage of 30 mg/(kg·d), and the sham surgery group and the model group were given equal volume of normal saline through intragastric administration. All three groups were given intragastric administration once a day, for seven consecutive days. Modified neurological severity score (mNSS) was used to evaluate neurological deficit; novel object recognition test (NORT) and Morris water maze (MWM) were used to evaluate the cognitive function; immunofluorescence was used to detect the expression of CD31 in cortex; Western blot was used to detect zonula occludens-1 (ZO-1), Occludin, Claudin-5, phosphorylated nuclear factor kappa-B (p-NF-κB), interleukin-1β (IL-1β) and tumor necrosis factor-α (TNF-α), transient receptor potential melastatin-2 (TRPM2), phosphorylated protein kinase B (p-Akt), phosphorylated glycogen synthetase kinase-3β (p-GSK3β) protein expression levels.Results(1) Neurological function: compared with the sham surgery group, mNSS in the model group significantly increased at the 1st, 3rd, 5th and 7th day (P<0.05); compared with the model group, mNSS in the 24A group significantly decreased at the 3rd and 7th day (P<0.05). (2) Cognitive function: compared with the sham surgery group, the NORT recognition index at 1st and 24th hour in the model group was significantly lower (P<0.05); compared with the model group, the 1-hour and 24-hour NORT recognition index in the 24A group significantly increased (P<0.05). Compared with the sham surgery group, the escape latency of the model group significantly prolonged and the number of times of crossing the platform significantly reduced from day 2 to day 4 after intervention (P<0.05); compared with the model group, the escape latency of the 24A group was significantly shortened from day 3 to day 4 after intervention, and the number of platform-site crossovers was significantly increased (P<0.05). (3) The expression of CD31, ZO-1, Occludin, Claudin-5 protein: the fluorescence expression of CD31 in the sham surgery group was dense and showed red fluorescence; compared with the sham surgery group, the fluorescence expression of CD31 in the model group significantly decreased (P<0.05). Compared with the model group, CD31 fluorescence expression in 24A group significantly increased (P<0.05). Compared with the sham group, ZO-1, Occludin and Claudin-5 protein expression levels in the model group significantly decreased (P<0.05). Compared with the model group, protein expression levels of ZO-1, Occludin and Claudin-5 in the 24A group significantly increased (P<0.05). (4) Protein expression of p-NF-κB, IL-1β, TNF-α, TRPM2, p-Akt, p-GSK3β: compared with the sham surgery group, the expression levels of p-NF-κB, IL-1β, TNF-α and TRPM2 in the model group significantly increased, while the expression levels of p-Akt and p-GSK3β significantly decreased (P<0.05). Compared with the model group, the expression levels of p-NF-κB, IL-1β, TNF-α and TRPM2 of the 24A group significantly decreased, while the expression levels of p-Akt and p-GSK3β significantly increased (P<0.05).Conclusion24A can effectively improve the neurological function and cognitive function, reduce inflammatory response and ameliorate BMECs damage of CI/RI mice, which may be related to the regulation of TRPM2/Akt/GSK3β pathway.